The Littlest angel's Easter [videorecording (DVD)] - Zipursky, Arnie; Delaney, Chris; Stewart, Elizabeth; Boone, Don; Judd, Naomi; Tazewell, Charles (Family classics., 2005)
Ryan Newman's move to a small town seems like a change for the worse--until he meets the Littlest Angel.